Close
Register
Close Window

Show Source |    | About   «  7.2. PDA Exercises   ::   Contents   ::   7.4. Deterministic Pushdown Automata  »

7.3. PDAs and Context Free Languages

7.3.1. PDAs and Context Free Languages

Let’s recap some important points that we have covered this semester.

  1. Regular languages are languages that can be recognized by DFAs or NFAs, or represented by a RegEx or a regular grammar. These are all equivalent and interchangable.

  2. Adding non-determinism to DFAs added no power in terms of the languages that can be recognized.

  3. Context-free languages (CFL) are those languages that can be represented by context-free grammars (CFG).

  4. Regular languages are a subset of context-free languages.

  5. PDAs have stack memory, and this allows them to recognize all regular grammars (just don’t use the stack), and some other languages that we have proved to be non-regular.

  6. A PDA can be deterministic (DPDA) or non-deterministic (NPDA).

In this module, we address the relationship between NPDAs and CFLs. Spoiler alert: NPDAs recognize CFLs.

Settings

Proficient Saving... Error Saving
Server Error
Resubmit

Now we want to show that given an NPDA, we can construct a CFG. But first, we will show a result to make the next proof easier.

Theorem: Given a NPDA \(M\), \(\exists\) a NPDA \(M'\) such that all transitions have the form \(\delta(q_i, a, A) = \{c_1, c_2, \ldots c_n\}\) where

\[\begin{split}\begin{eqnarray*} c_i &=& (q_j, \lambda)\\ \mbox{or}\ c_i &=& (q_j, BC)\\ \end{eqnarray*}\end{split}\]

Each move either increases or decreases stack contents by a single symbol.

Proof: (sketch)

lt7pf4

Theorem: If \(L = L(M)\) for some NPDA \(M\), then \(L\) is a CFL.

Want to show that each NPDA represents a CFL, so we will take a NPDA \(M\) and convert it to a CFG. It will be an easier construction if we take the NPDA and put all the transitions in a simpler form.

Proof:

Given NPDA \(M\), first, construct an equivalent NPDA \(M'\) that will be easier to work with. Construct \(M'\) such that
1. \(M'\) accepts if stack is empty
2. Each move increases or decreases stack content by a single symbol. (Can only push 2 variables or no variables with each transition.)
\(M' = (Q, \Sigma, \Gamma, \delta, q_0, z, F)\)
Construct \(G = (V,\Sigma, S, P)\) where
\(V = \{(q_icq_j)\ |\ q_i, q_j \in Q, c \in \Gamma \}\)
(Some of these variables will be useless.)
\((q_icq_j)\) represents “starting at state \(q_i\) the stack contents are \(cw, w \in \Gamma^*\), some path is followed to state \(q_j\) and the contents of the stack are now \(w\)”.
Goal: \((q_0zq_f)\) which will be the start symbol in the grammar.
Meaning: We start in state \(q_0\) with \(z\) on the stack and process the input tape. Eventually we will reach the final state \(q_f\) and the stack will be empty. (Along the way we may push symbols on the stack, but these symbols will be popped from the stack).
(NOTE: Machine accepts by empty stack, but it is such that there is only 1 final state in which the machine accepts by final state.)
To construct the productions in P:
1) Replace
lt8pf5
by
\[(q_iAq_j) \rightarrow a\]
where the stack changes are:
\[\begin{split}\begin{array}{lcclc} & q_i & \ \ (\mbox{some path}\ \rightarrow) \ \ & &q_j \\ \\ \mbox{stack:} & A && \mbox{stack:} & \\ & X_1 & && X_1 \\ & X_2 &&& X_2 \\ & \underline{X_n} &&& \underline{X_n} \\ \end{array}\end{split}\]
2) Replace
lt8pf6
by
\[(q_iAq_k) \rightarrow a(q_jBq_l)(q_lCq_k)\ \mbox{for all}\ q_l, q_k \in Q\]
\[\begin{split}\begin{array}{ccccccc} q_i & \ \ (\mbox{path}\ \rightarrow) \ \ & q_j &\ \ (\mbox{path}\ \rightarrow) \ \ & q_l &\ \ (\mbox{path}\ \rightarrow) \ \ & q_k \\ \\ &&B&& \\ A && C &&C \\ X_1 & & X_1 & & X_1 & & X_1 \\ X_2 && X_2 && X_2 && X_2 \\ \underline{X_n} &&\underline{X_n} &&\underline{X_n} &&\underline{X_n}\\ \end{array}\end{split}\]
This will create some useless variables, but that’s ok.
Must show that the constructed grammar \(G\) is such that \(L(G) = L(M')\). That is, \(w \in L(G) \mbox{iff}\ w \in L(M)\). (see book) QED.

Example 7.3.1

\(L(M) = \{aa^*b\}\), \(M = (Q, \Sigma, \Gamma, \delta, q_0, z, F)\), \(Q = \{q_0, q_1, q_2, q_3\}\), \(\Sigma = \{a, b\}, \Gamma = \{A, z\}\), \(F = \{\}\). \(M\) accepts by empty stack.

lt8pda7
Construct the grammar \(G = (V,T,S,P)\),
\(V = \{(q_0Aq_0), (q_0zq_0), (q_0Aq_1), (q_0zq_1), \ldots \}\)
NOTE: some variables may be useless.
\(T = \Sigma\)
\(S = (q_0zq_2)\)
\(P =\)
\[\begin{split}\begin{array}{crl} \mbox{From transition 1} & (q_0Aq_1) \rightarrow & b \\ \\ \mbox{From transition 2} & (q_1zq_2) \rightarrow & \lambda \\ \\ \mbox{From transition 3} & (q_0Aq_3) \rightarrow & a \\ \\ \mbox{From transition 4} & (q_0zq_0) \rightarrow & a(q_0Aq_0)(q_0zq_0)| \\ & & a(q_0Aq_1)(q_1zq_0)| \\ & & a(q_0Aq_2)(q_2zq_0)| \\ & & a(q_0Aq_3)(q_3zq_0) \\ & (q_0zq_1) \rightarrow & a(q_0Aq_0)(q_0zq_1)| \\ & & a(q_0Aq_1)(q_1zq_1)| \\ & & a(q_0Aq_2)(q_2zq_1)| \\ & & a(q_0Aq_3)(q_3zq_1) \\ & (q_0zq_2) \rightarrow & a(q_0Aq_0)(q_0zq_2)| \\ & & a(q_0Aq_1)(q_1zq_2)| \\ & & a(q_0Aq_2)(q_2zq_2)| \\ & & a(q_0Aq_3)(q_3zq_2) \\ & (q_0zq_3) \rightarrow & a(q_0Aq_0)(q_0zq_3)| \\ & & a(q_0Aq_1)(q_1zq_3)| \\ & & a(q_0Aq_2)(q_2zq_3)| \\ & & a(q_0Aq_3)(q_3zq_3) \\ \mbox{From transition 5} & (q_3zq_0) \rightarrow & (q_0Aq_0)(q_0zq_0)| \\ & & (q_0Aq_1)(q_1zq_0)| \\ & & (q_0Aq_2)(q_2zq_0)| \\ & & (q_0Aq_3)(q_3zq_0) \\ & (q_3zq_1) \rightarrow & (q_0Aq_0)(q_0zq_1)| \\ & & (q_0Aq_1)(q_1zq_1)| \\ & & (q_0Aq_2)(q_2zq_1)| \\ & & (q_0Aq_3)(q_3zq_1) \\ & (q_3zq_2) \rightarrow & (q_0Aq_0)(q_0zq_2)| \\ & & (q_0Aq_1)(q_1zq_2)| \\ & & (q_0Aq_2)(q_2zq_2)| \\ & & (q_0Aq_3)(q_3zq_2) \\ & (q_3zq_3) \rightarrow & (q_0Aq_0)(q_0zq_3)| \\ & & (q_0Aq_1)(q_1zq_3)| \\ & & (q_0Aq_2)(q_2zq_3)| \\ & & (q_0Aq_3)(q_3zq_3) \\ \end{array}\end{split}\]
Recognizing aaab in M:
\[\begin{split}\begin{eqnarray*} (q_0,aaab,z) & \vdash & (q_0,aab,Az) \\ & \vdash & (q_3,ab,z) \\ & \vdash & (q_0,ab,Az) \\ & \vdash & (q_3,b,z) \\ & \vdash & (q_0,b,Az) \\ & \vdash & (q_1, \lambda, z) \\ & \vdash & (q_2, \lambda, \lambda) \\ \end{eqnarray*}\end{split}\]
At this point stack is empty.
Derivation of string aaab in G:
\[\begin{split}\begin{eqnarray*} (q_0zq_2) & \Rightarrow & a(q_0Aq_3)(q_3zq_2) \\ & \Rightarrow & aa(q_3zq_2) \\ & \Rightarrow & aa(q_0Aq_3)(q_3zq_2) \\ & \Rightarrow & aaa(q_3zq_2) \\ & \Rightarrow & aaa(q_0Aq_1)(q_1zq_2) \\ & \Rightarrow & aaab(q_1zq_2) \\ & \Rightarrow & aaab \\ \end{eqnarray*}\end{split}\]
Meaning of first line in derivation is: \((q_0zq_2) \stackrel{*}{\Rightarrow} axy\) where \((q_0Aq_3)\stackrel{*} {\Rightarrow} x\) (which in the example above will eventually derive \(a\)) and \((q_3zq_2)\stackrel{*}{\Rightarrow} y\) (which in the example above will eventually derive \(ab\)).
Must show that the constructed grammar \(G\) is such that \(L(G) = L(M')\). That is, \(w \in L(G)\) iff \(w \in L(M)\). (see book) QED.

   «  7.2. PDA Exercises   ::   Contents   ::   7.4. Deterministic Pushdown Automata  »

nsf
Close Window